BS EN IEC 62841-2-18 AMDAA. Electric motor-operated hand-held tools, transportable tools and lawn and garden machinery. Safety. Part 2-18. Particular requirements for hand-held strapping tools (21st February 2022) - British Standards Institution,
No abstract available